PENGELOLAAN DESTINASI WISATA DI KAWASAN KONSERVASI PENYU KOTA PARIAMAN SUMATERA BARAT - Ramadhan, Mutiara; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Tourism is a strategic sector in regional development that contributes to economic growth and environmental conservation, including through the development of educational tourism with a focus on nature conservation. The Sea Turtle Conservation Area in Pariaman City is a tourist destination that not only serves as a sea turtle conservation center but also as an environmental education facility for the community and tourists. This study aims to analyze the management of the tourist area and identify the challenges that arise during the management process. The research approach used is qualitative-descriptive, with data collection through observation, interviews, and documentation. The main sources are the managers. The study results show that management is carried out based on the POAC management functions: planning for infrastructure development and educational programs, organizing tasks between departments, implementing educational and protection programs, and monitoring through regular coordination. Although management is functioning fairly well, there are several obstacles such as poorly maintained facilities, limited budgets, and a need to raise public awareness. Overall, the management of this conservation area has made a positive contribution to sea turtle protection and sustainable tourism development, but improvements are still needed in terms of facility maintenance and community participation. Keywords: Management, Sea Turtle Conservation, Educational Tourism, POAC, Pariaman City.